Application of boron reduces vanadium toxicity by altering the subcellular distribution of vanadium, enhancing boron uptake and enhancing the antioxidant defense system of watermelon - Fareeha Shireen; Muhammad Azher Nawaz; Junyang Lu; Mu Xiong; Mohsin Kaleem; Yuan Huang; Zhilong Bie (Ecotoxicology and Environmental Safety, 2021)
Vanadium (V) is the fifth most abundant transition metal, elevated levels of V are hazardous to plants. Boron (B) is an essential micronutrient for plants and can mitigate heavy metal toxicity. However, the mechanism used by B to promote tolerance to vanadium is unknown. In this study, a combination of physiological and gene expression analysis was used to explain mechanism of B (75 µM) induced V (40 mg L-1) stress tolerance in watermelon. V stress severely reduced root and shoot growth and increased the accumulation of ROS. B application improved tolerance to V by enhancing the expression of B transporter genes (ClaNIP5;1–1, ClaNIP5;1–2, ClaBOR4) that facilitated B uptake and transport while restricting V transport in plant tissues. At cellular level, the higher V retention in leaves was achieved by cell wall chelation, whereas, the higher V exclusion in vacuole of root cell was driven by elevated vacuolar H+-ATPase, H+-PPase activities, and transcript level of ClaVHP1;1, ClaPDR12–1 and ClaPDR12–2 genes facilitated by B application. Moreover, B application reduced tissue ROS cascade by enhancing antioxidant enzymatic activity and expression of superoxide dismutase (ClaCSD1–1, ClaCSD1–2, ClaCSD3, ClaMSD1) and catalase (ClaCAT2–1, ClaCAT2–2) genes that enhanced the defense mechanism of the V treated plants, improved root and shoot growth and tolerance index of watermelon. In conclusion, we demonstrate that ameliorative effect of B in tolerance to V of watermelon was based on B homeostasis and improved antioxidant defense system. These findings might help to increase watermelon production in V polluted soils.